2013
DOI: 10.1186/1471-2318-13-44
|View full text |Cite
|
Sign up to set email alerts
|

Age-related self-overestimation of step-over ability in healthy older adults and its relationship to fall risk

Abstract: BackgroundOlder adults could not safely step over an obstacle unless they correctly estimated their physical ability to be capable of a successful step over action. Thus, incorrect estimation (overestimation) of ability to step over an obstacle could result in severe accident such as falls in older adults. We investigated whether older adults tended to overestimate step-over ability compared with young adults and whether such overestimation in stepping over obstacles was associated with falls.MethodsThree grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 41 publications
9
79
3
1
Order By: Relevance
“…Previous studies utilizing the mental chronometry method have reported that the duration or distance of an imagined movement corresponds poorly to the duration or distance of the actual movement in elderly individuals3, 7, 8 ) . In the present study, we utilized a different method to evaluate judgment error in elderly individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies utilizing the mental chronometry method have reported that the duration or distance of an imagined movement corresponds poorly to the duration or distance of the actual movement in elderly individuals3, 7, 8 ) . In the present study, we utilized a different method to evaluate judgment error in elderly individuals.…”
Section: Discussionmentioning
confidence: 96%
“…As described above, overestimation of physical ability [26] is considered a potential fall risk. Therefore, we expected that the frequency of fall experiences in patients who overestimated their ability and had less anxiety in hospital would decrease after watching the animation movie.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, we found that patients overestimated their physical ability. Reportedly, overestimation of physical ability is a possible fall risk [26], and inadequate self-estimation resulted from unawareness of decreased physical status and fall risks [27]. Then, we asked patients how they estimated their own physical ability normally and in hospital.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…Several researchers have reported on the relationship between aging and judgment errors about physical ability and on the relationship between falls and judgment errors9,10,11, 15,16,17,18,19 ) . In these studies, several tasks were utilized to evaluate judgment errors of physical ability in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The assessments can be roughly divided into two types: spatially predictive tasks and temporally predictive tasks17 ) . The Functional Reach Test (FR) or other reaching tasks, step-over test, and maximum one stride length test are examples of spatially predictive tasks9, 10, 12, 17,18,19,20 ) . The Timed up and Go test (TUG), maximum gait speed, 20 step walking time, and single-leg standing are examples of temporally predictive tasks15,16,17 ) .…”
Section: Introductionmentioning
confidence: 99%